PERTANGGUNGJAWABAN PIDANA TERHADAP TINDAK PIDANA KORUPSI PADA PROGRAM KONPENSASI PENGURANGAN SUBSIDI BAHAN BAKAR MINYAK INFRASTRUKTUR PEDESAAN (STUDI PUTUSAN MA No. 2093 K / PID. SUS / 2011) - Anggi P. Harahap; Mahmud Mulyadi; Madiasa Ablisar; Marlina Marlina (USU LAW JOURNAL, 2015)
ABSTRACT Corruption can take place anywhere, in state institutions, in private institutions, and also in daily life. Combating corruption requires treatment and prevention in an integrated manner with the proper functioning of the legal system of the law and legal institutions in the criminal justice system. Based on the results of this research criminal liability against corruption is the liability of the offenses committed by the offender. Someone will be held accountable for these actions when there is an element in the action against the law and there is no excuse and fault elements must be met in terms of combating corruption. This is due to the principle of liability in criminal law that is not tobe punishment if no fault. Criminal act and criminal liability for acts of corruption in the PKPS BBM-IP activities in Simalungun where to defendant has been proven legally and convincingly, the defendant is able to be responsible and there is no excuse any fault that may negate or justification which can eliminate the unlawful nature of the act, the criminal liability for acts of corruption in the form of sentencing of offenders as set forth in the Supreme Court decision on the appeal. Keywords : corruption, criminal liability